Characterization of microstructure and mechanical properties of titanium -based bioactive ceramics laser-deposited on titanium alloy. Issue 19 (1st October 2022) - Wang, Chengdong; Wang, Yueping; Bao, Zhenlin; Dong, Jianjun; Geng, Yan; Liu, Shufan; Wang, Chuanyang; Nie, Ping
Abstract: Titanium-Based Bioactive Ceramics (TBBC), obtained by laser deposition of Ti and hydroxyapatite (HAp) powders, are the preferred materials for the clinical application of mandibular implants which are beneficial for bone tissue regeneration. So far, the bonding strength of TBBC fabricated by traditional additive manufacturing techniques reported in literature is no more than 35 MPa. Therefore, the main problem that restricts the application of this material on the mandible is the low bonding strength with the matrix. Unfortunately, the effective method to improve the bonding strength of TBBC is rarely mentioned. Under this circumstance, TBBC fabricated on artificial mandible are prone to peeling off during the bite and chew. In order to improve the mechanical properties of materials without losing the biological activity, this paper firstly studied the interaction mechanism between laser beam and Ti-HAp mixed powders. Afterward, two major crack avoidance factors, dilution rate and overlap rate, were analyzed to determine the optimal laser deposition parameters for TBBC. Finally, the mechanical performances were comprehensively studied. Of course, the biological activity of the TBBC was also preliminarily evaluated in Simulated Body Fluid (SBF). The results show that the fabricated TBBC have a bonding strength of 177.3–338.6 MPa, at least 5 times higher than the traditional process of 35 MPa. Furthermore, the increase of the maximum mass ratio of HAp powders to 15% will generate the bio-phase of Ca3 (PO4 )2, which provides a better Ca/P environment with PO4 3− needed for bone tissue regeneration.